Power to the people?: The impact of decentralization on governance - Dreher, Axel (KOF working papers, 2006)
The paper analyzes the impact of decentralization on governance employing four indicators of governance and five measures of decentralization. Depending on data availability, crosssections for a maximum of 129 countries are estimated. Results for a panel of about 70 countries over the period 1984-2001 are also presented. The results show that decentralization - measured as the share of sub-national employment, revenues or, respectively, expenditures - improves governance. This is particularly true for low income countries but - depending on the indicator employed - to some extent for high income countries also. However, the number of sub-national government tiers exerts a negative impact on some dimensions of governance. -- Decentralization ; Governance ; Legal Quality ; Judicial Independence ; Federalism ; Institutions